Зародження чернечого самітництва в Галлії у V ст. (на прикладі «Vita Patrum Jurensium») (І) - Бондарюк, Б. М. (Давнина. Харківський історико-археологічний щорічник, 2016)
SummaryB. Bodnariuk. Formation of the monastic anchoret in Gallia in the V  с. (on example «Vita Patrum Jnrensium») (I)This article deals with questions connected with the process of the appearing and formation of Christian monastic anchoret on the territory of Gallia in the V  c. Besides that, the author analyses the peculiarities and characteristic features of ascetic practice of the first Gallian anachorets, using the facts contained in the «Living of Jurassic Paters».